Enhanced lipid and biomass production using alcohol wastewater as carbon source for Chlorella pyrenoidosa cultivation in anaerobically digested starch wastewater in outdoors. (January 2018) - Tan, Xiao-Bo; Zhao, Xian-Chao; Zhang, Ya-Lei; Zhou, Yue-Yun; Yang, Li-Bin; Zhang, Wen-Wen
Highlights: Alcohol wastewater (AW) used as carbon source for microalgae mixotrophic growth. Outdoor cultures were processed using raw wastewater in several tanks. Moderate addition of AW significantly improved biomass and lipid production. Abstract: Alcohol wastewater (AW) as carbon source for enhancing Chlorella pyrenoidosa growth and lipid accumulation in anaerobically digested starch wastewater (ADSW) was performed in outdoor cultivation. The biomass and lipid production significantly increased while adding optimal amount of AW (AW/ADSW = 1:15) during exponential phase. In comparison with blank ADSW culture, the optimal AW addition increased the biomass production, lipid content and productivity by 35.29%, 102.68% and 227.91%, respectively. However, AW addition caused severe bacterial contamination and the total bacterial increased by 4.62-fold. Simultaneously, the optimal consortia of microalgae/bacteria effectively removed nutrients from the wastewater, including 405.18 ± 36.47 mg CODCr /L/day, 49.15 ± 5.54 mg N/L/day and 6.72 ± 1.24 mg P/L/day.